2012
DOI: 10.1111/j.1365-3148.2012.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

The granulocytes in neutropenia 1 (GIN 1) study: a safety study of granulocytes collected from whole blood and stored in additive solution and plasma

Abstract: GASP has a similar safety profile to other sources of granulocytes for patients with refractory infection or in need of secondary prophylactic transfusion. Further studies are required to clarify the role of GASP in the treatment of neutropenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…The exact role of granulocyte transfusions (whether derived from whole blood or collected by apheresis) therefore remains unclear. In the UK, a recent study reported on the safety of the use of a component derived from whole blood donations, and recruitment included 13 children (Massey et al , ). The reaction profile was similar to that with other granulocyte components and all the children recovered.…”
Section: Transfusions To Infants and Childrenmentioning
confidence: 99%
“…The exact role of granulocyte transfusions (whether derived from whole blood or collected by apheresis) therefore remains unclear. In the UK, a recent study reported on the safety of the use of a component derived from whole blood donations, and recruitment included 13 children (Massey et al , ). The reaction profile was similar to that with other granulocyte components and all the children recovered.…”
Section: Transfusions To Infants and Childrenmentioning
confidence: 99%
“…The “Granulocytes in neutropenia 1” (GIN 1) [46], a multicenter study from the U.K., evaluated the safety of transfusing pooled, whole blood-derived granulocytes. The product (“granulocytes in additive solution and plasma”: GASP) is obtained by combining 10 buffy coats (obtained from 10 blood donations) with 400 mL of platelet additive solution and re-centrifuging [25].…”
Section: Gtx For Treatment Of Infection: Review Of Recent Studies (Pomentioning
confidence: 99%
“…The EFS is considering preparing granulocytes from whole blood granulocytes as prepared by the NHSBT in England. Regulatory approval for such a blood product will be requested by the end of 2017.…”
Section: Francementioning
confidence: 99%